Impact of Energy Consumption and Environmental Pollution in Malaysia - Haruna, Muhammad Aminu; Mahmood, Suraya (Energy Economics Letters, 2019)
Increasing concerned by authorities in developed and developing economies on environmental cleanness cause government additional spending. Economic activities are achieved at the cost of environmental pollution and degradation. The aim of this study is to investigate how energy use affects the environment in the short and long run and government effort to deal with the resulting effect in Malaysia. This paper develops autoregressive distributive lag (ARDL) approach in analyzing the time series data from 1980-2017. The results show that energy consumption affect the environment in short and the long run and government spending do little to tackle the problem. The study proposes a shift from existing energy use to energy friendly by investing in renewable energy among others.